HAM DALAM RUANG DOMESTIK Studi terhadap UU. No. 23 Tahun 2004 Tentang PKDRT - Shulton Asnawi, Habib (Al-Mawarid Jurnal Hukum Islam, 2010)
This article describes about Domestic Violence: Perspectives of the Act. No. 23 of 2004 on Domestic Violence: An Effort In the Struggle for Human Rights "Human Rights". Womens issues that dimapankan for several generations until today is in line with the process of strengthening the traditional Islam (classical), which tend to be conservative and literal in understanding the religious messages and doctrines that exist, patiarkhi an established cultural constructs are universally and lasts for centuries, and the justification of authority backed by the state law. Therefore, this condition resulted in follow-up of violence by husbands against wives. Domestic violence (domestic violence) can be positioned as a result of which was born from a gender biased social system. All forms of violence, particularly Domestic Violence (Domestic Violence) is a violation of human rights (human rights), and the evil of human dignity and a form of discrimination that must be removed. Keywords:gender, ketidakadilan, kekerasan dalam rumah tangga, kebijakan pemerintah dan hak asasi manusia.